Folly of Sky, Earth, Man: The Work of Yatsuka Hajime - Dana Buntrock (Oz, 1999)
Japanese names are revealing; choice of script may suggest a word as indigenous or not, and render a Japanese concept more foreign or visa-versa. Many architects, although Yatsuka is not among them, fabricate words, relying on the meaning of Japanese characters.